Translanguaging in Mathematics Bilingual Classroom: Students' Perception - Geminastiti Sakkir; Hajrah Hajrah; La Sunra (PT ARRUS Intelektual Indonesia, 2024)
This research aims to investigate translanguaging in a Bilingual classroom. Hence, this research tries to know the students’ perception of translanguaging classroom interaction. This research focused on the student’s perception of translanguaging. This research applied a qualitative method, the instruments were interviews. The result of the interview was transcribed and analyzed based on the research focus. The findings of this research show that translanguaging facilitates the teaching and learning of the Mathematic bilingual program makes their English teaching in the classroom effective and makes the students understand the teaching and learning material well. The way lecturers conduct translanguaging is based on the situation of the students. If the students do not understand what the lecturers explain in English, they will use translanguaging in the classroom to make the teaching and learning process. Students have positive responses about the bilingual practice in Mathematics class.